2008
DOI: 10.1038/ajh.2008.254
|View full text |Cite
|
Sign up to set email alerts
|

Leptin, Blood Pressure, and Aerobic Capacity in Women

Abstract: Circulating leptin concentrations are related to body fatness, but the hypertensive influence of leptin is modified by physical fitness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…However, based on the medical literature, several mechanisms have been proposed to explain the BP-raising effect of leptin, 5,[29][30][31] and in particular the leptin-induced increased activity in the sympathetic nervous system has been in focus as a BP-raising mechanism. We found a significant interaction between hyperleptinemia and level of physical activity, as reported elsewhere, 18 which may explain why physical fit overweight subjects can stay normotensive. Finally, it should be noted that BMI also was an independent predictor of new-onset hypertension, so other factors than leptin are involved in overweight-related hypertension.…”
Section: Perspectivessupporting
confidence: 64%
See 1 more Smart Citation
“…However, based on the medical literature, several mechanisms have been proposed to explain the BP-raising effect of leptin, 5,[29][30][31] and in particular the leptin-induced increased activity in the sympathetic nervous system has been in focus as a BP-raising mechanism. We found a significant interaction between hyperleptinemia and level of physical activity, as reported elsewhere, 18 which may explain why physical fit overweight subjects can stay normotensive. Finally, it should be noted that BMI also was an independent predictor of new-onset hypertension, so other factors than leptin are involved in overweight-related hypertension.…”
Section: Perspectivessupporting
confidence: 64%
“…Finally, possible interactions regarding leptin and adiponectin were investigated, in particular a possible interaction between leptin and level of physical activity, as reported elsewhere. 18 …”
Section: Definition Of New-onset Hypertensionmentioning
confidence: 99%
“…The high risk of developing cardiovascular diseases in obese subjects has also drawn attention to study the neurohormonal effects of leptin on cardiac functioning and remodeling. A relationship between the circulating leptin level with hypertension and associated cardiovascular morbidity has been reported recently (3,7,8). Kramer et al (9) also observed increased leptin levels among hypertensive elderly subjects and reported that higher leptin level increases 70% chances of risks for subsequent hypertension.…”
Section: Introductionmentioning
confidence: 83%
“…Recently, Patel et al (7) also reported positive association between leptin and DBP. The relationship between leptin and hypertension was also studied by Sabatier et al (8), and their results illustrated that leptin-mediated actions may be diminished not only by reducing leptinproducing adipose tissue, but also by increasing physical activity in individuals with high levels of adiposity. Another recent study (9) has reported increased leptin levels among hypertensive elderly subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between leptin concentrations and aerobic PF was previously presented by Kiviniemi et al [22] but was not observed by others [23,41]. Sabatier et al [40] studied women and found however that the cardiovascular consequence of leptin and fatness through increased arterial pressure can be diminished by the level of PF.…”
Section: Discussionmentioning
confidence: 80%